Application of semifluidized bed bioreactor as novel bioreactor system for the treatment of palm oil mill effluent (POME) - Abass O., Alade; Jameel, Ahmad Tariq; Suleyman, Aremu Muyibi; Mohamed Ismail, Abdul Karim; Alam, Md Zahangir (Academic Journals, 2011)
Palm oil mill effluent (POME) is a high strength organic wastewater, which adversely affects aquatic life as well as human life directly or indirectly. This has attracted concern due to the rapid expansion of the oil palm industries in countries such as Malaysia and Indonesia, which currently contribute about 80% of the world palm oil. The conventional bioreactors such as pond digester, anaerobic filtration, up-flow anaerobic sludge blanket (UASB), up-flow anaerobic sludge fixed-film (UASFF), continuous stirred tank reactor (CSTR), anaerobic contact digestion and fluidized bed, used over the past decades are largely operated anaerobically. They have been reported to be less effective for the treatment of the increasing volume of POME as well as meeting the new stringent wastewater treatment standards. Therefore, treatment method such as aerobic under a continuous system is anticipated to be effective alternative to the defects observed in the previously employed bioreactors. The use of semifluidized bed bioreactor containing immobilized cells for the biodegradation of various high strength organic wastewater have been reported as highly efficient treatment method. Thus, to address the increasing environmental impact of POME in the producing nations, the application of semifluidized bed bioreactor as a novel technology in the palm oil industry will be of immense benefit, economically and environmentally.